Penentuan Nilai Efektivitas Mesin Small Press Line A Melalui Overall Equipment Effectiveness (OEE) di PT. Mekar Armada Jaya - Sigit Sulistio, Tri; Rosyidi, M. Imron; Rifa’i, Affan; Muh Widodo, Eko; Rusdjijati, Retno (Universitas Muhammadiyah Magelang, 2023)
Small Press Machine Line A in the Stamping & Tools Division of PT. Mekar Armada Jaya produces car and body parts as effectively as possible to increase productivity. However, the performance of the machine and the maintenance system that is carried out is not comprehensive on aspects of the Small Press Machine and takes a long time, causing high machine downtime, this affects the smooth running of the production process. Therefore, measuring effectiveness uses Method the Overall Equipment Effectiveness (OEE), Six Big Losses and Failure Mode Effect Analysis (FMEA). Research results for January 2021 – December 2022, namely the A1 Machine is 82%, the A2 Machine is 76% and the A3 Machine is 58%. The loss factor of the three machines is caused by Equipment Failure Loss (equipment damage loss). The results of the analysis using the FMEA method show that the failures that often occur in the three machines include the engine having an over stroke, the work method is due to the visual check method, and the engine has been repaired by an AIDA technician. So, it is suggested that in order to increase the effectiveness of the Small Press Line A machine, the Stamping & Tools Division should apply FMEA method to look for components or processes that have failed, whether humans, machines, work methods, or materials.